Microbial mats as model to decipher climate change effect on microbial communities through a mesocosm study - Mazière, C.; Duran, R.; Dupuy, C.; Cravo-Laureau, C. (Frontiers in Microbiology, 2023)
Marine environments are expected to be one of the most affected ecosystems by climate change, notably with increasing ocean temperature and ocean acidification. In marine environments, microbial communities provide important ecosystem services ensuring biogeochemical cycles. They are threatened by the modification of environmental parameters induced by climate change that, in turn, affect their activities. Microbial mats, ensuring important ecosystem services in coastal areas, are well-organized communities of diverse microorganisms representing accurate microbial models. It is hypothesized that their microbial diversity and metabolic versatility will reveal various adaptation strategies in response to climate change. Thus, understanding how climate change affects microbial mats will provide valuable information on microbial behaviour and functioning in changed environment. Experimental ecology, based on mesocosm approaches, provides the opportunity to control physical-chemical parameters, as close as possible to those observed in the environment. The exposure of microbial mats to physical-chemical conditions mimicking the climate change predictions will help to decipher the modification of the microbial community structure and function in response to it. Here, we present how to expose microbial mats, following a mesocosm approach, to study the impact of climate change on microbial community.